1972
DOI: 10.2466/pr0.1972.30.1.263
|View full text |Cite
|
Sign up to set email alerts
|

Implied Threat and the Territorial Factor in Personal Space

Abstract: Body territory may be a useful concept when personal space is studied under conditions of threat. It is predicted that, under conditions implying physical threat, defense of body territory will be greatest in the condition of male-to-male movement, that the male object-person will be a greater source of threat than the female object-person, and that anxiety will be associated with greater intervening distances for both sexes. Each S (male or female) approached and was approached by his respective object-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Since sex has been found to be a factor in personal space (2,4), it is believed that the sex factor was not as strong in this particular study because of the experimental manipulations. In the present study there were no references to the subjects about sex or attractiveness, and this, coupled with the fact that the 0 s made no effort to be particularly sexually appealing, attenuated the sex variable.…”
Section: Standing Objectmentioning
confidence: 87%
See 2 more Smart Citations
“…Since sex has been found to be a factor in personal space (2,4), it is believed that the sex factor was not as strong in this particular study because of the experimental manipulations. In the present study there were no references to the subjects about sex or attractiveness, and this, coupled with the fact that the 0 s made no effort to be particularly sexually appealing, attenuated the sex variable.…”
Section: Standing Objectmentioning
confidence: 87%
“…By contrast, Dosey and Meisels (4) told their subjects that they were to approach an object person who would evaluate their physical attractiveness. Bailey et al (2) chose their object persons on the basis of physical attractiveness and thereby accentuated the sex variable.…”
Section: Standing Objectmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that 90% vegetative cover for this part of Michigan is forest land composed of conifer and hardwoods ranging in age up to 250 + years [USDA 1960, Shetron 2000. Reclamation of tailing basins in this part of Michigan will represent an "OASIS" in the midst of a desert [Bailey 1972]. Bailey's desert refers to forested landscapes, which do not have the diversity for sustaining a rich population of wildlife.…”
Section: Ems -----------·-------Kg/ha----------·-··-------mentioning
confidence: 99%
“…Willis (1966) found sex, age, and extent of friendship to be important personal space variables, with women, younger persons and intimates being more closely approached. Bailey, Harnett, and Gibson (1972) reported that when males approached females, they invaded their personal space to a greater extent than when women approached men. In another study, observers interpreted the meaning of personal space invasion differently when the violator was a woman rather than a man.…”
mentioning
confidence: 99%